Annual dynamics of the ground beetle community in two beech stands in Mavrovo National Park - Hristovski, Slavčo; Prelik, Dana; Cvetkovska, Aleksandra; Melovski, Ljupčo; Ivanov, Gjorgji (Macedonian Journal of Ecology and Environment, 2005)
The results of the investigation on annual dynamics of ground beetle community (Coleoptera, Carabidae) in two localities (Bunec and Shunteski Rid) in beech association Calamintho grandiflorae-Fagetum in Mavrovo National Park (western Macedonia) are presented in this paper. Bunec stand was under stronger anthropogenic pressure while the Shunteski Rid was better preserved (although managed) beech stand. The investigation was conducted in the period of April to November 2002. The material was collected by pitfall traps and qualitative and quantitative composition of the ground beetle community was determined (number, seasonal dynamics, biomass and sexual structure). The influence of the forest degradation level on the ground beetle community was discussed, based on the qualitative and quantitative criteria.